Exploring Trends and Advancements in Financial Distress Prediction Research: A Bibliometric Study - Sethi, Soumya Ranjan; Mahadik, Dushyant Ashok; Bilolikar, Rajkiran V. (International Journal of Economics and Financial Issues, 2024)
Due to the growing complexity and unpredictability of contemporary markets as evidenced by the financial crisis of the past ten years, the field of financial distress prediction (FDP) research is receiving more attention. For creditors, investors, and other stakeholders to make well-informed decisions on their financial relationships with a given entity, financial distress prediction is essential. This paper identified the risk indicators that are the cause of financial distress and latest tools and methods to predict financial distress with identifying the risk management strategies for eradicate the distress condition. In this context, this study explores the landscape of the literature published in this area. We have used systematic and bibliometric approach for studying the existing literature. For the study, we have collected articles from the Scopus database for the period 1985 to 2022. Science mapping technique has been used for the analysis data has been conducted with the help of Vosviewer and Biblioshiny software. Various important component of a literature review like most relevant authors, most relevant sources, keywords co-occurrence network, thematic analysis and others have been explored. The study will help the scholars and future researchers in getting a comprehensive understanding and insights in the concerned field and add to the existing body of literature.